Resurrecting minimal Yukawa sector of SUSY SO(10) - K. S. Babu; Borut Bajc; Shaikh Saad (Journal of High Energy Physics, 2018)
Abstract Supersymmetric SO(10) models with Yukawa coupling matrices involving only a 10 H and a 126 ¯ H $$ {\overline{126}}_H $$ of Higgs fields can lead to a predictive and consistent scenario for fermion masses and mixings, including the neutrino sector. However, when coupled minimally to a symmetry breaking sector that includes a 210 H and a 126 H , these models lead either to an unacceptably small neutrino mass scale, or to non-perturbative values of the gauge couplings. Here we show that with the addition of a 54 H to the symmetry breaking sector, the successful predictions of these models for fermion masses and mixings can be maintained. The 54 H enables a reduction of the B − L symmetry breaking scale to an intermediate value of order 1012 GeV, consistent with the observed neutrino mass spectrum, while preserving perturbative gauge coupling unification. We obtain an excellent fit to all fermion masses and mixings in this framework. We analyze carefully the prediction of the model for CP violation in neutrino oscillations. Consistency with proton lifetime, however, requires a mini-split SUSY spectrum with the squarks and sleptons having masses of order 100 TeV, accompanied by TeV scale gauginos and Higgsinos. Such a spectrum may arise from pure gravity mediation, which would predict the partial lifetime for the decay p → ν ¯ K + $$ p→ \overline{ν}{K}^{+} $$ to be an order of magnitude above the current experimental limit.